Holidays at home - Camping and glamping as a part of domestic tourism: An overview and analysis of camping (and in particular luxury camping) as an alternative form of domestic tourism in the time of the coronavirus - Kristina Sommer (IUBH Internationale Hochschule, 2020)
Camping is a part of the outdoor hospitality industry. It is a popular activity and an emerging tourism sector in Europe. Camping has changed from being a cheap form of travel to a real outdoor experience. Travelling with a tent is popular, but recreation vehicles and caravans have become an increasingly important area of focus. The demand for more luxurious and larger caravans is growing. Camping grounds must now deal with the new demands of their customers, who wish to have more comfortable and luxurious options. It is no longer enough to just provide washing and cooking facilities. The demand for wellness and sports facilities, once found primarily in the hotel industry, is now increasing at camping sites. This trend is called "glamping" - a portmanteau of the words "glamorous" and "camping". As the name suggests, comfort and luxury are the essential characteristics of glamping. Glamping combines an outdoor experience with the comfort of a hotel and is a new segment in the camping tourism industry. The coronavirus crisis in particular has shown that camping and glamping are alter-native types of domestic tourism which could provide a chance to generate new customer segments.
Keywords: Z31; 330; Camping; Glamping; Domestic Tourism; Camping Ground; Camping Tourism; Nature-Based Tourism; Outdoor Hospitality Industry